Confinement of Magnetic Skyrmions to Corrals of Artificial Surface Pits with Complex Geometries - Matsumoto, Takao; Shibata, Naoya (Frontiers in Physics, 2022)
Magnetic skyrmion is a particle-like swirling spin texture promising for future memory devices. The geometric confinement and artificial control of skyrmions are crucial for such practical applications. In a previous research, we developed a technique to confine skyrmions to simple geometric corrals, such as a rectangle and a triangle, composed of artificial surface pits with nanometer-scale dimensions fabricated by using a focused electron beam. The technique has a potential advantage of facilitating more complex geometries, which has not been fully explored yet. Here we directly visualize skyrmions confined to surface-pit corrals with several complex geometries by using differential phase contrast scanning transmission electron microscopy. We find that individual skyrmions are deformed not only in shape but also in size under a moderate-bias field. We also find that deformed skyrmionic spin textures with opposite polarities coexist in the zero-field condition. The present study provides a guide to confine skyrmions, which should be useful for future applications.